Penciptaan Desain Tote Bag Bertema Prangko Seri Bangunan Bersejarah Kota Medan Sebagai Cendramata Pos Bloc Medan - Fahmi Alkindi; Raden Burhan Surya Nata Diningrat (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
Medan City has many historical buildings that reflect its rich culture and history. However, with the times, public awareness of this cultural heritage is diminishing. One of the efforts to preserve and reintroduce the historical buildings in Medan is through the creation of souvenir designs. This research focuses on the creation of a tote bag design with the theme of historical building series stamps of Medan City as souvenirs at Pos Bloc Medan. The creation method used in this research refers to the stages of exploration, design, and realization. Exploration was conducted by studying the visual and historical elements of historical buildings in Medan City, such as Maimun Palace, Medan Post Office, and Al-Mashun Grand Mosque. Designing is done by adapting the shape of stamps as the main design concept, combining digital illustrations with interesting color compositions. The final result is a tote bag design featuring historical buildings in the format of stamp illustrations, printed with digital printing techniques. This research is expected to contribute to the effort of preserving Medan City's cultural heritage through creative media, as well as increasing public awareness of the importance of preserving and appreciating historical buildings. In addition, this tote bag design also has the potential to become an attractive souvenir product with educational value for tourists and local communities.